The Effect of Manganese Greensand Addition on Tray Aerator to Reduce COD Levels of Laundry’s Wastewater - Naufal Adi Nugroho; Sulistiyani Sulistiyani; Nikie Astorina Yunita Dewanti (Universitas Diponegoro, 2021)
COD level of Pojok Laundry’s wastewater did not meet the quality standard regulated in the Special Region of Yogyakarta Regulation No. 7 of 2016 (>150 mg/l) which was 442.5mg/l. This study was aimed to decrease COD levels using the tray aerator method. Manganese greensand with a diameter of 0.25 mm and a thickness of 2.4 cm/tray was also added. This type of research was a quasi-experimental with Nonequivalent Control Group Design. The sample in this study amounted to 50 samples with 5 treatments (30, 45, 60, 75, and 90 minutes), and 5 repetitions. Samples were taken from the washing machine outlet pipe. There were two groups, where the control group was only given aeration and the treatment group was given aeration with the addition of manganese greensand. Data analysis using the two-way ANOVA test showed that there was an effect of time variations on the decrease in COD levels (p<0.05), there was a difference in the average of decreased levels of COD between the control and treatment groups (p<0.05). The average decrease in COD levels after treatment with a time of 30, 45, 60, 75, and 90 minutes, respectively, was 195.7 mg/l (28.80%); 299.0 mg/l (43.63%); 372.1 mg/l (54.79%); 438.3 mg/l (64.61%); and 513.8 mg/l (75.45%). The decrease in COD levels increased with time. The conclusion of this research was that tray aerator with manganese greensand addition can reduce COD levels with the highest reduction up to 76.69% (90 minutes treatment, detergent usage: 30 g).